2014
DOI: 10.1136/vr.102302
|View full text |Cite
|
Sign up to set email alerts
|

Presence of superantigen genes and antimicrobial resistance in Staphylococcus isolates obtained from the uteri of dairy cows with clinical endometritis

Abstract: Clinical endometritis is an important disease of dairy cattle and results in decreased reproductive performance. This disease is caused by contamination of the uterus with a broad spectrum of microorganisms after calving. In this study, staphylococcal isolates from the uterus of dairy cows with clinical endometritis were tested for their distribution of superantigen (SAg) genes and antimicrobial resistance. Between the 127 staphylococcal isolates collected in this study, 10 species were identified. The predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Staphylococcus aureus , a typical representative of Gram‐positive bacteria, is one of the major pathogens of many human and animal inflammatory diseases, including endometritis . LTA, a specific endotoxin embedded in the cell wall of S. aureus , has been reported to activate the inflammatory response .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus , a typical representative of Gram‐positive bacteria, is one of the major pathogens of many human and animal inflammatory diseases, including endometritis . LTA, a specific endotoxin embedded in the cell wall of S. aureus , has been reported to activate the inflammatory response .…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus ( S. aureus ) is an opportunistic Gram‐positive bacterium that causes various infectious diseases in humans and animals , such as skin and soft‐tissue infections , as well as pneumonia , sepsis and endometritis , and has led to high mortality. LTA is a teichoic acid extracted from the Gram‐positive bacteria cell wall that is the predominant driving force of the host inflammatory response to this type of bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies (Fang et al 2019) demonstrated that SEC can directly cause inflammation, proinflammatory cytokine production and tissue damage in mammary glands, suggesting that SEC might play an important role in the development of mastitis associated with S. aureus infection. Clinical endometritis, which leads to decreased reproductive performance, is also an important disease in dairy cows (Jiang et al 2019;Zhao et al 2014). Zhao et al investigated SAg gene distribution of staphylococcal isolates in uterus of cows with clinical endometritis.…”
Section: Bovine Mastitis and Endometritismentioning
confidence: 99%
“…PCR analysis showed that most of isolates (63.0%) had at least 1 SAg gene. The most common SAg genes and genotypes were selj and sec-selj-sen (Zhao et al 2014). These results indicated that Staphylococci recovered from cows with clinical endometritis contained extensive and complex SAg genes, suggesting that SAg may contribute to the pathogenicity of bacteria in bovine endometritis.…”
Section: Bovine Mastitis and Endometritismentioning
confidence: 99%
“…S. aureus is a well-known gram-positive bacteria, which can lead to inflammation from both community-acquired and nosocomial infections [ 19 , 20 ]. S. aureus is also the main pathogenic microbe that causes endometritis and enhances the expression of proinflammatory cytokines [ 21 ]. It has been shown IFN- τ has immunomodulatory properties [ 22 ].…”
Section: Introductionmentioning
confidence: 99%